Resolving conflicting social categories: The role of age-related executive ability. - Hutter, Russell R. C.; Wood, Chantelle; Dodd, Georgina F. (British Journal of Psychology, 2012)
We investigated the effect of age-related decline in executive ability on the application of emergent features to incongruent social category conjunctions (e.g., male midwife). When forming an impression of an incongruent conjunction, older adults used more emergent attributes (attributes associated exclusively with the category conjunction and not the constituents), relative to younger adults. Moreover, this relationship was mediated by a reduction in inhibitory ability (measured using a Stroop task) and processing speed (measured using a Digit Symbol Substitution Test, DSST). These findings are consistent with the notion that executive ability is pivotal in understanding social functioning in older adults. We discuss the implications of these findings for the continuing development of models outlining the processes and stages involved in perceiving social category conjunctions.